Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahaan Bidang Manufaktur - Astuti; Lestari, Tina (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of this study is to determine the effect of liquidity level and profitability on company value. The method used is multiple regression analysis to determine the effect of each independent variable, namely liquidity and profitability, on the value of the company. This study was analyzed using correlation techniques using the SPSS 26 application. The results showed that the liquidity variable did not have a significant effect because there was no significant relationship between liquidity and company value, and the most influential variable was profitability because it showed that there was a significant relationship between profitability and company value. To increase the value of the company, there needs to be continuous attention to profitability because of its significant influence on the value of the company. Further research can be carried out in other industrial sectors, and research samples and variables can be examined using different measurement approaches.